1984
DOI: 10.1159/000163267
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response against Vaccinia Virus in Rhesus Monkeys: No Evidence for Primary MHC-Restricted Cytolytic T Cells

Abstract: Rhesus monkeys were tested in vitro for their cellular immune response after infection with vaccinia virus, employing lymphocyte preparations from various lymphoid tissues. Although virus-infected target cells were lysed by lymphoid cells from immunized, but not from uninfected, rhesus monkeys, we could neither find evidence for MHC-restricted T cells nor for antibody-dependent cellular cytotoxicity. Kinetics of target cell lysis, the killing patterns of immune lymphocytes measured on syngeneic, allogeneic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…CTL responses following infection with poxviruses have been documented in a number of species, including mice, rats, rabbits, and sheep (2,7,12,16,18,31). However, CTL responses to vaccinia virus have not been well characterized in nonhuman primates or in humans (22,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CTL responses following infection with poxviruses have been documented in a number of species, including mice, rats, rabbits, and sheep (2,7,12,16,18,31). However, CTL responses to vaccinia virus have not been well characterized in nonhuman primates or in humans (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic activity peaked at 5 to 7 days postinfection and was present in T-cell-depleted but not in T-cell-enriched fractions. The investigators concluded that NK-like, not HLA-restricted, T-cell activity was generated in lymphoid organs of rhesus monkeys after vaccinia virus infection (26). Recently, Graham et al used UV-inactivated vaccinia virus-infected fibroblasts to stimulate immune PBMC in vitro to detect specific CTL responses in revaccinated humans, and no convincing vaccinia virus-specific CTL activity was observed (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTL lyse virusinfected cells prior to virus maturation, thereby containing the spread of the infection within the host (521). The primary generation of poxvirus-specific CTL has been detected in many different species, including mice, rats, rabbits, and sheep, but not hamsters or primates (205,231,233,327,328,371,423,447,514,522). Although authentic human leukocyte antigen-restricted T cells specific for vaccinia virus have not previously been detected in the peripheral blood of primates (371,447), it is likely that with cell enrichment and isolation procedures currently available, one could isolate CTL clones.…”
Section: Adccmentioning
confidence: 99%
“…Earlier studies failed to detect vaccinia-specific cytotoxic T lymphocytes (CTLs) either in non-human primates or in humans [19][20][21], although poxvirus-specific CTLs were described in animal models [22,23]. Perrin et al advanced the hypothesis that non-T cytotoxic lymphocytes bearing Fc receptors and acting in the presence of specific antibodies were responsible for the vaccinia-virus cytotoxic activity observed in the PBMCs (peripheral blood mononuclear cells) of vaccinia-immune healthy humans [19].…”
Section: T Cell Compartmentmentioning
confidence: 99%